Earnings inequality in Europe: structure and patterns of inter-temporal changes - Ioannis Cholezas; Panos Tsakloglou (Institute for the Study of Labor (IZA), 2007)
The paper provides an analysis of the level, the structure and the patterns of inter-temporal change in hourly earnings inequality in Europe. For the purposes of static inequality decomposition analysis, the data of the ECHP are employed. Considerable cross-country differences are observed across the EU regarding both the level and the structure of earnings inequality. In most countries, of the four factors examined (education, age, sex and sector of employment), education and, to a lesser extent, age are found to be most closely associated with inequality. For the purposes of inequality trend decomposition analysis national data sets for eight European countries are utilised. The results show that in most countries the main factor behind the observed changes in earnings inequality was changes in inequality within groups irrespective of the partitioning criterion used, while the effect of changes in group mean earnings was negligible. Finally, changes in the composition of wage and salary earners regarding the four aforementioned factors (education, age, sex and sector of employment) had a relatively large, but not uniform across countries, effect only in a few countries and mainly when the partitioning factor is education
urn:nbn:de:101:1-20080416263
Keywords: 330; Lohnstruktur; Einkommensverteilung; Soziale Mobilität; EU-Staaten